Trade Policy Issues and Developments - Kirmani, Naheed (Occasional Papers; Occasional Paper ;, 1985)
This paper discusses the salient features of recent developments and outlines the prospects for trade policy by highlighting the main issues that will determine the scope and timing of liberalization under a possible new General Agreement on Tariffs and Trade (GATT) round of multilateral trade negotiations. As the more advanced developing countries acquire the skills and investments to diversify exports toward more sophisticated manufactured products, restrictions against them tend to multiply. These not only impede the export prospects of the developing countries directly affected, but also slow specialization and diversification, thus severely affecting the smaller developing country exporters. Across-the-board protectionist measures have been avoided in the industrial countries because it is widely acknowledged that trade restrictions and protectionism are inappropriate responses to exchange rate developments. Exchange rate movements reflect financial flows as well as trade flows, and the importance of exchange rates that correspond to underlying economic fundamentals is unquestioned.